Explaining the Link Between Alcohol and Homicides: Insights from the Analysis of Legal Cases in Lithuania - Laura Miščikienė; Justina Trišauskė; Mindaugas Štelemėkas; Kristina Astromskė (Medicina)
Background and Objectives: Alcohol consumption has been a longstanding public health concern and known link to violence. The aims of this study were to analyze alcohol-related homicide cases in Lithuania, focusing on the prevalence of binge drinking among perpetrators and victims, the situational and behavioral patterns leading to violence, and the legal outcomes of these cases. Materials and Methods: This study employed a retrospective analysis of court case law of criminal cases of the year 2019. The analysis was conducted by combining qualitative and quantitative analytical approaches. Results: The findings revealed that 84.6% of homicides occurred during binge drinking events. Alcohol intoxication was prevalent among both perpetrators (92.3%) and victims (86.5%), emphasizing the dual role of alcohol in homicide cases. Interpersonal violence was the primary pattern of homicide (78.8%), while planned homicides accounted for 21.2%. Thematic content analysis of the cases revealed that Lithuanian courts consistently regard alcohol consumption as an aggravating factor that contributes to the commission of violent crimes and influences the severity of criminal punishment. This reflects a judicial position that voluntary intoxication does not lessen legal responsibility, despite its effects on impairing judgment, heightening aggression and impulsivity, and escalating conflicts into deadly violence. Conclusions: Our findings revealed that the majority of alcohol-involved homicides occurred during binge drinking events, in a domestic environment, and because of unplanned acts of interpersonal violence. Targeted public health interventions should focus on strengthening alcohol control policies and enforcing stricter regulations to discourage binge drinking environments.